The transversal archive as the axis of producing the new journalistic content in Spain. A case study of the public broadcasters RNE and EITB - Rodríguez Reséndiz, Perla Olivia; Martínez Costa, María del Pilar (Historia y Comunicación Social, 2024)
Radio is seeking to maintain its leadership and adapt to new ways of generating and disseminating audio content. In response to this need, radio archives, considered for decades as the last stronghold of production, are acquiring notoriety since they are part of the sound patrimony. This article aims to know, based on the case study of two public service broadcasters in Spain, the management and potential use of radio archives and to determine their relevance in the production of new journalistic content. The results demonstrate that although the process has been prolonged in time, the archive is integrated in a transversal mode, as a dynamic, agile, versatile, and vital element of journalistic production.
Keywords: Radio archive; radio journalist; radio programs; public radio; radio production